Direito de propriedade, atividades econômicas e contexto institucional no Vale do Jari - Claro, Priscila Borin de Oliveira (2008)
Does titling influence individual choices in favor of sustainable activities? This question addresses the role of property rights definition on individual economic choices. Definition of rights, however, does not guarantee sustainability. Individual preferences are also influenced by the market, the capacity of governance, and the public policies created and implemented by the State. The objective of this research is to characterize the economical choices of private agents and the institutional environment, in a historical perspective, at the Jari Valley. It is a qualitative research based on case study methodology. Data was collected from secondary and primary sources. Interviews were conducted with semi structured questionnaires with employees of Orsa Group, Cajari Extractive Reserve representatives, local community representatives, local leaders and researchers. We can conclude that the definition of the title can not guarantee sustainable use of forest resources and local development. Public policies on land occupation and local development are also important factors that influence economic choices. Moreover, enforcement of rights, with regards to monitoring activities and punitive decisions are crucial factors that influence agents behavior. At the Jari Valley public policies, that aimed local development, were based on occupation of land at any cost. State centralized most of the decisions and local communities could not participate in public police making. Centralized decision impeded the development of local leadership, collective action and the development of local economy based on sustainable forest products.